Identity Changes and Consumer Behavior. How Becoming Parents Changes Our Consumption Choices - Cito, Maria Cristina <1982> (Alma Mater Studiorum - Università di Bologna, 2015)
This research aims at investigating the impact of the identity change on consumption. An identity change is defined as the acquisition of a new identity after a life change event. For instance after the birth of the first child the new identity as parent is acquired and a woman can define herself as a mother. Despite marketing research recognizes that individuals’ identity is unstable and susceptible to change, the investigation of the identity change is still in its infancy. Furthermore, marketing research did not investigate the contextual effect of the new as well as the old identity on individuals’ reaction toward identity-marketing. In order words, whether people show a more favorable reaction toward product related to their new or their old identities after an identity change is still unclear. In order to answer this question, five studies are conducted. Results show that when the new identity substitutes the old one, people show a more positive reaction toward new-identity related products, while when the new identity is added to the old ones, people show a more positive reaction toward old-identity related products. This is the case also when the new identity accounts for high levels of identification (study three) and when the old identity is squeezed by the new one (studies four and five). A new concept, the identity strain, is then introduced and discussed.